2007
DOI: 10.1097/pas.0b013e31802b86f8
|View full text |Cite
|
Sign up to set email alerts
|

Translocation and Expression of CSF1 in Pigmented Villonodular Synovitis, Tenosynovial Giant Cell Tumor, Rheumatoid Arthritis and Other Reactive Synovitides

Abstract: We recently demonstrated that CSF1, the ligand of the tyrosine kinase receptor, CSF1R, can be translocated in pigmented villonodular synovitis (PVNS) and tenosynovial giant cell tumor (TGCT). In this study, we evaluated the staining characteristics of PVNS/TGCT and reactive synovitides for CSF1 and CSF1R by in situ hybridization and immunohistochemistry on tissue microarrays and correlated these findings with the recently described translocation. We collected specimens of TGCT/PVNS from 60 patients and of rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
139
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(146 citation statements)
references
References 6 publications
6
139
1
Order By: Relevance
“…Combined CSF1 immunohistochemistry and FISH demonstrated that only the cells with the translocation expressed CSF1 while the majority of cells neither carried the translocation nor expressed CSF1. Interestingly, Cupp et al, (2007) recently studied 57 cases of TGCT/PVNS; all were found to express CSF1 mRNA and/or CSF1 protein, including 22 cases (39%) that lacked the CSF1 translocation, suggesting that alternative mechanisms may lead to up-regulation of CSF1. Nevertheless, the COL6A3-CSF1 fusion transcripts identified in the present study are unlikely to produce a functional protein containing the receptor-binding part of CSF1, which is required for the mechanism described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Combined CSF1 immunohistochemistry and FISH demonstrated that only the cells with the translocation expressed CSF1 while the majority of cells neither carried the translocation nor expressed CSF1. Interestingly, Cupp et al, (2007) recently studied 57 cases of TGCT/PVNS; all were found to express CSF1 mRNA and/or CSF1 protein, including 22 cases (39%) that lacked the CSF1 translocation, suggesting that alternative mechanisms may lead to up-regulation of CSF1. Nevertheless, the COL6A3-CSF1 fusion transcripts identified in the present study are unlikely to produce a functional protein containing the receptor-binding part of CSF1, which is required for the mechanism described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI effectively indicated bone lesions, articular cartilage lesions, and osteophytes in the joint cavity, which is helpful in determining whether arthroplasty is necessary. Therefore, we consider MRI to be useful in the diagnosis of PVNS and in determining the choice of surgical modalities, although pathological examination is needed in addition to MRI to accurately distinguish PVNS from rheumatoid arthritis, degenerative osteoarthropathy, synovial haemangioma, and other disorders [9].…”
Section: Discussionmentioning
confidence: 99%
“…Chromogenic RNA ISH was also used in these cases to assess CSF1 mRNA expression. The protocols for FISH and ISH have been previously described (11,17). The results of CSF1 break-apart FISH were determined by analyzing a minimum of 25 lesional cells, based on nuclear size and location within the tumor.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the aims of this study on the pathogenesis of malignant D-TSGCTs were 2-fold: first, by fluorescent in situ hybridization (FISH) and in situ hybridization (ISH), we investigated whether translocation and mRNA overexpression of the CSF1 gene also occur in malignant D-TSGCTs, as reported previously in benign TSGCTs (11,17). Second, we assessed whether malignant phenotypes of D-TSGCTs are attributed to the deregulated early G 1 and G 1 -S transition checkpoints and/or non -random chromosomal aberrations, like other tumors with a specific chimeric oncogene (e.g., Ewing sarcoma; ref.…”
mentioning
confidence: 99%